RETRACTED: Profile of Children with Covid 19 Infection in our Set Up - Baljinder kaur; Navpreet kaur (International Journal of Coronaviruses, 2021)
This article has been retracted on July 20, 2022. VIEW THE RETRACTION NOTICE (https://doi.org/10.14302/issn.2692-1537.ijcv-25-5866) In December 2019, a novel coronavirus, now named as SARS-CoV-2, caused a series of acute atypical respiratory diseases in Wuhan, Hubei Province, China. The disease caused by this virus was termed COVID-19. The virus is transmittable between humans and has caused pandemic worldwide. The number of death tolls continues to rise and a large number of countries have been forced to do social distancing and lockdown. In humans, COVIDs mostly cause respiratory and gastrointestinal symptoms. Clinical manifestations range from a common cold to more severe disease such as bronchitis, pneumonia, severe acute respiratory distress syndrome, multi-organ failure and even death. Preliminary evidence suggests children are just as likely as adults to become infected with SARS-CoV-2 but are less likely to be symptomatic or develop severe symptoms. in our study , we consider the symptomatology , complications and mortality patterns of this disease in children.
Keywords: SARS-CoV